Doping of Ni in MIL-125(Ti) for enhanced photocatalytic degradation of carbofuran: Reusability of coated plates and effect of different water matrices. (December 2021) - Samy, Mahmoud; Gar Alalm, Mohamed; Fujii, Manabu; Ibrahim, Mona G.
Abstract: Nickel has been recently recognized as an efficient dopant to improve the electronic structure of metal-organic frameworks (MOFs). Herein, we prepared Ni-doped MIL-125(Ti) MOFs with different Ti: Ni molar ratios to evaluate the role of Ni in the improvement of photocatalytic degradation of carbofuran in different water matrices. The characterization of the TiNi MOF structure confirmed the successful incorporation of Ni 2+ in the lattice structure of MIL-125(Ti). The molar ratio of 1:1 showed the highest degradation of carbofuran compared to pristine MIL-125(Ti) and mixed 2:1 TiNi MOF. We used the response surface methodology (RSM) to optimize the operating parameters of the photocatalytic reaction indicating that a pH of 11, irradiation intensity of 104.6 W/m 2, and catalyst loading of 0.44 g/L were the optimal conditions. Furthermore, we employed the photocatalyst in a retained form by coating aluminum plates using polysiloxane to evaluate the reusability of the catalyst without needing a post-collection of nanoparticles. The effect of interfering species in different water matrices was investigated by conducting the photocatalytic reaction in different water backgrounds such as lake, tap, drain, and sea waters. The mechanism of photocatalytic oxidation was investigated by several scavenging experiments to identify the effective reactive oxidant species (ROS) and the degradation pathways were proposed by liquid chromatography coupled with tandem mass spectrometry LC/MS-MS. The toxicity of the generated intermediates was evaluated using the ecological structure activity relationships (ECOSAR) software. Graphical abstract: Unlabelled Image Highlights: Doping of Ni in MIL-125(Ti) improved the photocatalytic degradation of carbofuran. The photocatalytic degradation in different water matrices was evaluated. The operating parameters were optimized by RSM. TiNi MMOF coated plates showed high stability and reusability in consecutive cycles.